Historical perspectives and emerging trends in fentanyl use: Part 1 – Pharmacological profile - Stanila Stoeva-Grigorova; Maya Radeva-Ilieva; Nadezhda Karkkeselyan; Stela Dragomanova; Gabriela Kehayova; Simeonka Dimitrova; Maria Petrova; Snezha Zlateva; Petko Marinov (Pharmacia)
Fentanyl, a potent synthetic opioid, is widely used for severe pain management and anesthesia but poses significant risks due to its extreme potency and addictive potential. It acts primarily on μ-opioid receptors, with additional effects on κ- and δ-receptors, producing analgesia and adverse effects, such as respiratory depression, mediated via G-protein and β-arrestin signaling pathways. Fentanyl’s pharmacokinetics include rapid onset and a short duration, with extensive liver metabolism via CYP3A4 enzymes. Its high lipophilicity allows it to cross the blood-brain barrier quickly, contributing to its rapid central nervous system effects and associated risk of respiratory depression. Despite its therapeutic value, fentanyl’s potential to induce tolerance and dependence, coupled with escalating illicit use, underscores the need for enhanced prevention strategies, improved overdose management, and stricter regulatory measures to balance therapeutic utility with abuse prevention.